DNA barcoding species inventory of Microgastrinae wasps (Hymenoptera, Braconidae) from a Mexican tropical dry forest - Fernández Flores, Sofía (2013)
The cosmopolitan Microgastrinae is probably the most diverse braconid subfamily of parasitoid wasps, yet its species diversity is far from being known. As part of a global initiative for DNA barcoding Microgastrinae species, here we show the results of a study that assessed the species richness of this subfamily in a Mexican tropical dry forest located in the Chamela region, near the Pacific coast of Jalisco. Barcoding sequences of a total of 551 microgastrine specimens were generated, corresponding to 238 haplotypes. Performance of two species delineation approaches, a 2% corrected pairwise distance criterion and the general mixed Yule-coalescent (GMYC) method, yielded 100 and 112 putative species, respectively, which belong to 13 genera. The species delimited by the above two approaches were mostly congruent with our morphospecies identification. Ten molecular operational taxonomic units (MOTUs) were split into twenty-two species by the GMYC approach. We found morphological differences between the GMYC species corresponding to three of these MOTUs. Thus, a total of 103 microgastrine species were confirmed for the region of study. Thirty-three species were only represented by males, and therefore, their generic assignment is only tentatively proposed. A new record for the country is provided for the Diolcogaster-basimacula species group. Based on a comparison of nearly 20 000 barcoding sequences released for Microgastrinae from 75 countries, only five microgastrine species from Chamela were found to occur in other countries, four in Costa Rica and one in Canada and the United States.